2015
DOI: 10.1007/s10654-015-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk for childhood leukemia associated with maternal and paternal age

Abstract: The role of reproductive factors, such as parental age, in the pathogenesis of childhood leukemias is being intensively examined; the results of individual studies are controversial. This meta-analysis aims to quantitatively synthesize the published data on the association between parental age and risk of two major distinct childhood leukemia types in the offspring. Eligible studies were identified and pooled relative risk (RR) estimates were calculated using random-effects models, separately for childhood acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 32 publications
5
41
0
1
Order By: Relevance
“…Our findings for ALL largely affirm the results of previous studies which reported an increased risk of ALL with older maternal age [79, 16, 19]. However, our results contradict the strong association between older paternal age (45+) and ALL that persisted with adjustment for maternal age in a recent registry-based Danish cohort study [10].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings for ALL largely affirm the results of previous studies which reported an increased risk of ALL with older maternal age [79, 16, 19]. However, our results contradict the strong association between older paternal age (45+) and ALL that persisted with adjustment for maternal age in a recent registry-based Danish cohort study [10].…”
Section: Discussionsupporting
confidence: 84%
“…In terms of acute myeloid leukemia (AML), there was a U-shaped risk with maternal age and the risk of AML was increased only in offspring born to younger fathers. Only 4 of the 77 studies included in this analysis examined the impact of mutual adjustment for maternal and paternal age, and the only notable association that persisted with mutual adjustment was an increased risk of AML with younger maternal age [7]. …”
Section: Introductionmentioning
confidence: 99%
“…In the context of the current CLIC study, a meta-analysis was undertaken [22] showing positive associations of advanced age of both parents at birth of the index child with ALL in the offspring irrespective of study design. Subsequently, registry-based, record-linkage nested case-control (NCC) studies from the US and Denmark also reported an increased ALL risk with advanced maternal age, whereas the positive associations with older paternal age were marginally significant [2326].…”
Section: Introductionmentioning
confidence: 99%
“…The association between maternal age and risk of childhood leukemia has been studied in several studies over more than half a century, but the results are inconsistent. A recent meta‐analysis found that the mother's age is a risk factor for childhood leukemia . The association between paternal age and risk of childhood leukemia has also been studied, yet to a much more limited extent and mostly over the last two decades.…”
Section: Introductionmentioning
confidence: 99%